PENERAPAN KONSEP DASAR MANAJEMEN PERKANTORAN DALAM PENDIDIKAN: STUDI KASUS PADA PENGELOLAAN DOKUMEN DAN ARSIP SEKOLAH - Herdi; Sri Murningsih; Triyono Widodo; Ilham Isroni Isron; Meyti Suryandari (STKIP Subang, 2024)
This study aims to analyze the application of basic office management concepts in document and archive management in schools and its impact on administrative efficiency and education quality. Proper management of documents and archives is a crucial aspect of office management that can enhance the accessibility, security, and organization of school data. Using a qualitative method, this study found that the adoption of digital technology in archive management and the development of human resources through training significantly influence the effectiveness of school administration. However, challenges such as budget constraints, infrastructure limitations, and resistance to change remain obstacles to the optimal implementation of office management. The study results indicate that schools with strong leadership and a clear vision in office management are more successful in overcoming these challenges, thus improving the quality of administrative services and supporting the overall enhancement of educational quality. Keywords: office management, document and archive management, education quality.